2017
DOI: 10.1186/s13071-017-2199-0
|View full text |Cite
|
Sign up to set email alerts
|

Symbiont dynamics of the Tibetan tick Haemaphysalis tibetensis (Acari: Ixodidae)

Abstract: BackgroundCharacterization of the microbial diversity and symbiont dynamics of ticks may help to understand the development of ticks and reveal new strategies to control tick-transmitted pathogens, which has not yet been explored in the Tibetan tick Haemaphysalis tibetensis. This tick species is widely distributed in the Tibetan Plateau, and is recognized as one of the primary parasites affecting domestic and wild animals.MethodsIn the present study, the endosymbionts of H. tibetensis were characterized using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Again, no bacteria were detected in salivary glands (Fig. 2C1) (13,14,25,27,28). To examine the presence and abundance of these species in lab-reared H. longicornis and R. haemaphysaloides, we quantified their relative abundance by real-time PCR using genus-specific primers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Again, no bacteria were detected in salivary glands (Fig. 2C1) (13,14,25,27,28). To examine the presence and abundance of these species in lab-reared H. longicornis and R. haemaphysaloides, we quantified their relative abundance by real-time PCR using genus-specific primers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…turanicus after CLE proliferation and colonization in ovaries ( Lalzar et al, 2014 ). Additional studies have shown that CLE are more abundant in ovaries and Malpighian tubules, but less abundant in other organs as salivary glands ( Noda et al, 1997 ; Lalzar et al, 2014 ; Wang et al, 2017 ; Buysse et al, 2019 ). As Rh.…”
Section: Impact Of Symbionts On Tick Physiologymentioning
confidence: 99%
“…They are notorious vectors that can transmit various pathogens (viruses, rickettsiae, bacteria, spirochaetes and protozoans) among arthropods [ 1 , 2 ]. With climate change, new tick-borne pathogens and tick-borne diseases have become severe threats to public health all over the world [ 3 , 4 ]. With a high reproductive potential, the fully engorged female can lay up to several thousand eggs [ 5 ].…”
Section: Introductionmentioning
confidence: 99%